1996
DOI: 10.1007/bf00862054
|View full text |Cite
|
Sign up to set email alerts
|

Girls prone to urinary infections followed into adulthood. Indices of renal disease

Abstract: This study describes blood pressure and renal function, as well as indices of renal disease, in females with and without renal scarring followed from their first urinary tract infection (UTI) in childhood. Of the 111 patients with a median follow-up time of 15 years, 54 had renal scarring (reflux nephropathy) on urography, which was severe in 19 and moderate in 35. The glomerular filtration rate was lower in patients with severe renal scarring and correlated with renal area on urography. However, the filtratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 17 publications
1
41
0
2
Order By: Relevance
“…In the Parker and Kunin [5] study, hypertension was noted at follow-up in only ∼15% of the women. A recent study of women with scarring visible on renal scan also confirmed that the incidences of renal insufficiency and hypertension were lower than had previously been reported [13].…”
Section: Discussionsupporting
confidence: 60%
“…In the Parker and Kunin [5] study, hypertension was noted at follow-up in only ∼15% of the women. A recent study of women with scarring visible on renal scan also confirmed that the incidences of renal insufficiency and hypertension were lower than had previously been reported [13].…”
Section: Discussionsupporting
confidence: 60%
“…Of the adults in our follow-up study, only 6% presented under the age of 1 year compared with 78% of those in a recent Gothenburg study; the long-term outcome for these children will be of considerable importance[41]. They also report a good outcome, even in those with renal scarring, of a group of 111 women followed for a mean of 15 years from their first UTI in childhood[42].The study reported here indicates that the adult outcome for children with VUR carefully managed in childhood was very good in the great majority, even when VUR persisted at the end of childhood. Deterioration of renal function or blood pressure occurred almost exclusively in those with renal scarring and was usually predictable in childhood.…”
mentioning
confidence: 66%
“…In one study, the incidence of CRI in 30 adults who were diagnosed with severe renal scarring as children was 10% [42]. Another study of 294 patients (mean age at presentation, 17.2 years) with reflux nephropathy found a 2% incidence of CRI (glomerular filtration rate [GFR] < 40-69 mL/min) at presentation that increased to 24% at last follow-up (mean age, 34.2 years).…”
Section: Renal Insufficiencymentioning
confidence: 94%